OR12-02 When the Glucocorticoid Receptor Meets the Mineralocorticoid Receptor in the Nucleus of Human Cells - Petrillo, Maria G (J Endocr Soc, 2020)
Adrenal corticosteroids, such as glucocorticoids and mineralocorticoids, are indispensable for mediating response to stress, development, limiting inflammation, and maintaining energy and fluid homeostasis. These hormones exert their actions via binding to two closely related nuclear receptors, the glucocorticoid receptor (GR) and mineralocorticoid receptor (MR). The GR has low affinity for corticosteroids, but is expressed in nearly every cell. In contrast, the MR shows a higher affinity for corticosteroids and its expression is largely confined to those tissues where electrolyte exchange and fluid balance are required. GR and MR act as ligand-activated transcription factors which, following interaction with co-regulators and DNA responsive elements, either promote or repress gene transcription. The affinity for the same ligands, structural homology, and binding to the same DNA regions suggest GR and MR can compensate for each other’s actions. Yet, there are specific glucocorticoid and mineralocorticoid-mediated responses indicating GR-MR functional diversity. To investigate this interplay, we developed U-2 OS (human osteosarcoma) cell lines stably expressing GR, MR, and both GR and MR (GRMR). Immunofluorescence analysis showed that treatment of these cell lines with 1 nM of the synthetic glucocorticoid dexamethasone (Dex) induced nuclear traslocation of GR and MR. Conversely, treatment with 1 nM of aldosterone (Aldo) promoted nuclear translocation of the MR only. Moreover, Proximity Ligation Assay revealed that, in the absence of ligand, GR associated with MR in the cytoplasm and, upon 1 nM Dex exposure, GR-MR dimers were detected in the nucleus of GRMR cells. Surprisingly, nuclear GR-MR dimers were also detected in the presence of Aldo, suggesting that it is necessary to activate at least one receptor to induce nuclear traslocation of the heterocomplex. To decipher the functional contribution of GR-MR dimers in the transcriptional response of GR to Dex and MR to Aldo, we performed RNA-seq in GR, MR, and GRMR cells treated with 1 nM of Dex or Aldo. Transcriptome analysis revealed that Dex-activated GR regulated the transcription of 6180 genes. Co-expression of MR resulted in a blunted Dex-mediated gene response which affected only 1608 genes, suggesting a functional antagonism of MR. Aldo-activated MR regulated the transcription of 1660 genes. However, co-expression of GR expanded the Aldo-mediated gene response to 3150 genes. Strikingly, 74% of these genes were also regulated by Dex via GR, suggesting that GR-MR dimers in the presence of aldosterone are able to mimic the glucocorticod transcriptional response. Our data suggest that the role of distinct GR and MR homo- and hetero-dimers is relevant for regulating gene expression. Dissecting the mechanism and investigating the cross-talk between GR and MR may be useful to understanding these two receptors in heath and disease.